Penerapan Model Pembelajaran Cooperative Script Dalam Meningkatkan Keterampilan Menyimak Siswa Sekolah Dasar - Yati, Hafni; Syahrul Rizal, Muhammad (Science and Education Journal (SICEDU), 2024)
This research aims to improve students' listening skills through a cooperative script model for class I students at UPT SD Negeri 026 Pangkalan Kapas for the 2023/2024 academic year. The type of research used is Classroom Action Research. This research consisted of 2 cycles and each cycle was held in 2 meetings. Data analysis techniques are carried out using qualitative and quantitative descriptions. This research was carried out in 2 cycles, each cycle lasting 2 meetings. The results showed that students' listening skills improved after the action. The results of the research show that the use of the cooperative script model can improve the listening skills of class I students at UPT SD Negeri 026 Pangkalan Kapas. This is shown by an increase in the number of students who reach the minimum completeness criteria (KKM) and an increase in the average class and classical scores. The average value and percentage of classical completion in cycle I, meeting I, was 28.57%, in cycle I, meeting II, 57.14% and in cycle II, meeting I, 71.42%, in cycle II, meeting II, 85.71%.